Designing robust routing protocols to protect base stations in wireless sensor networks. Issue 17 (3rd October 2012) - Chen, Juan; Zhang, Hongli; Du, Xiaojiang; Fang, Binxing; Yan, Liu
ABSTRACT A base station is the controller and the data‐receiving center of a wireless sensor network. Hence, a reliable and secure base station is critical to the network. Once an attacker locates the base station, he or she can do many damages to the network. In this paper, we examine the base station location privacy problem from both the attack and defense sides. First, we present a new attack on base station: parent‐based attack scheme (PAS). PAS can locate a base station within one radio (wireless transmission) range of sensors in high‐density sensor networks. Different from existing methods, PAS determines the base station location on the basis of parent–child relationship of sensor nodes. Existing base station protection schemes cannot defend against PAS. Second, on the basis of PAS, we propose a two‐phase parent‐based attack scheme (TP‐PAS). Our simulation results demonstrate that TP‐PAS is able to determine the base station successfully in both low‐density and high‐density sensor networks. Then, to defend against PAS and TP‐PAS, we design a child‐based routing protocol and a parent‐free routing protocol for sensor networks. Our theory analysis and experiment results show that the parent‐free routing protocol has more communication cost and less end‐to‐end latency compared with the child‐based routing protocol. Copyright © 2012 John Wiley & Sons, Ltd.